Study of electron energy distribution functions (EEDFs) in three DC low-pressure plasma sources - Antonova, T; Bougrov, G; Bougrova, A; Choi, WK; Goncharov, L; Jung, HJ; Koh, SK; Kondranin, S; Kralkina, E; Sitin, E; Obukhov, V (JAPAN J APPLIED PHYSICS, 1998)
In the present paper the possibility of application of the regularization method for reliable determination of the position and form of structural features of electron energy distribution is considered. The regularization method is used in the processing of the probe characteristics, measured in gas discharge chambers of broad beam gridded Xe ion sources, with peripheral and with divergent magnetic fields, as well as in an ion accelerator with closed electron drift. Electron energy distribution functions with secondary maxima are observed in the plasma devices.